Pengabdian Mandiri Terintegrasi dengan Kuliah Kerja Nyata Tematik Covid-19 - Sudarman; Rachman , Dzul; Khatimah, Khusnul; Rahmawati, Yeni (Wadah Inovasi Indonesia, 2023)
Kuliah Kerja Nyata (KKN) is an integral part of higher education curriculum in Indonesia, aimed at implementing the principles of the 1945 Constitution and related education laws. KKN involves students living and working in rural areas to assist in community development, aligning with the goals of higher education. However, due to the COVID-19 pandemic, KKN activities have been adapted for online implementation, with limited participation from specific university programs. Despite challenges, KKN remains a valuable experience for students, contributing to their personal and academic growth. Three distinct KKN activities were carried out: English Weekly Meeting, a webinar on sports during the pandemic, and a COVID-19 health equipment donation program. Each activity faced its own set of challenges, including student participation and logistical issues. In conclusion, KKN is a vital component of higher education in Indonesia, fostering community engagement and practical learning. To improve future KKN experiences, clearer communication between universities and students, stronger cooperation with partner schools, and optimized program execution are recommended.